Novel Christmas Branched Like NiO/NiWO4/WO3 (p–p–n) Nanowire Heterostructures for Chemical Sensing. (2nd July 2021) - Kaur, Navpreet; Zappa, Dario; Maraloiu, Valentin‐Adrian; Comini, Elisabetta
Abstract: Establishing a platform comprising different nanostructured oxides is an emerging idea to develop highly sensitive and selective sensing devices. Herein, novel 3D‐heterostructures (p–p–n) consisting of 1D nanowires of NiO and WO3 along with their intermediate reactive product, i.e., NiWO4 seed, are produced by a two‐steps vapor phase growth method. In‐depth morphological and structural investigations describing the growth mechanism of these heterostructures are presented. Finally, the p–p–n heterostructures are integrated into conductometric sensing devices and their performances are investigated toward different gases. It is observed that by modulating the charge‐carrier transport with temperature, the heterostructure sensors exhibit selective behavior toward different gas analytes. Indeed, at 300 °C, the heterostructure sensors show relatively selective behavior toward NO2, while at 400 °C, high selectivity toward VOCs is observed. The improvement in sensing performances is mainly based on charge carrier transport through the two interfaces (one at WO3 /NiWO4 (n–p) and the other at NiWO4 /NiO (p–p)) and the modulation of charge carriers in the electron depletion layer of WO3 and hole accumulation layer of NiO and NiWO4 . The remarkable performance of these complex heterostructures with low ppb‐level detection limits makes them excellent candidates for chemical/ gas sensing applications in e‐noses. Abstract : A simple, high yield two‐step vapor‐phase growth method is implemented for the fabrication of novel heterostructures of ( p/p/n ) NiO/NiWO4 /WO3 . These heterostructures exhibit excellent sensing performance toward different oxidizing and reducing gases by modulating their optimal working temperature and charge carrier transport and hence show a high potential to use in e‐nose application.